Genomic Determinants of PI3K Pathway Inhibitor Response in Cancer - Downward, Julian; Weigelt, Britta (Frontiers in Oncology, 2012)
The phosphoinositide 3-kinase (PI3K) pathway is frequently activated in cancer as a result of genetic (e.g. amplifications, mutations, deletions) and epigenetic (e.g. methylation, non-coding RNA overexpression/downregulation) aberrations targeting its key components. Several lines of evidence demonstrate that tumours from different anatomical sites depend on the continued activation of this pathway for the maintenance of their malignant phenotype. The PI3K pathway therefore is an attractive candidate for therapeutic intervention, and inhibitors targeting different components of this pathway are in various stages of clinical development. Burgeoning data suggest that the genomic features of a given tumour determine its response to targeted small molecule inhibitors. Importantly, alterations of different components of the PI3K pathway may result in distinct types of dependencies and response to specific therapeutic agents. In this review, we will focus on the genomic determinants of response to PI3K, dual PI3K/mTOR, mTOR and AKT inhibitors in cancer identified in preclinical models and clinical trials to date, and the development of molecular tools for the stratification of cancer patients.